Analysis of the Judge's Considerations Regarding the Rejection of the Wonosari Religious Court's Marriage Dispensation Application - Yusnia, Nufrinda Shita; Mudiparwanto, Wahyu Adi (LEGAL BRIEF, 2024)
This article examines the problem, firstly how the judge considers the rejection of the marriage dispensation application. Second, what is the judge's interpretation regarding the urgent reasons for rejecting the application for marriage dispensation. This research is normative-empirical research with qualitative methods. The types of primary and secondary data are direct field data and literature studies. The research results show that the judge decides whether to reject or grant a request for marriage dispensation based on whether or not the reasons are urgent. Currently there is no concrete explanation regarding the urgent reasons, causing legal uncertainty and disparities in judges' decisions. Hopefully there is certainty regarding the urgent reasons in marriage dispensation cases so that judges in examining, adjudicating and deciding on marriage dispensation cases do not experience disparity in judges' decisions.